Family Financial Management as a Means of Household Welfare and Harmony for Residents - Iwan Fakhruddin; Dwi Winarni*; Luthfi Zamakhsyari (Universitas Lancang Kuning, 2023)
Good family financial management can create household prosperity and harmony. A prosperous household has a positive impact on its members and ultimately has an impact on the welfare of society at large. The role of women in the household is not only as wives and mothers but also as financial role models and decision-makers in managing daily finances. If you don't have expertise in managing finances, you are prone to experiencing domestic conflict. This community service aims to provide training and understanding of family financial management to members of the 'Aisyiyah Kembaran. The method used is training with the PRA approach, which aims to involve participants in the process of identifying problems, implementing solutions, and analyzing evaluations. The result is an increase in skills and understanding of family financial management that can be applied to every family. Thus, household conflicts can be avoided due to poor financial management.